PERAN FINANCIAL LITERACY DALAM MENINGKATKAN FINANCIAL WELL-BEING DI ERA DIGITAL - I Gusti Kade Birawan; Hidayat, Rahmat; Juhaeni, Unes (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
This study examines the role of financial literacy in improving digital financial well-being among Indonesian youth, considering financial behavior as a mediating variable and risk perception in fintech usage. Using a quantitative survey method, data was collected from 300 respondents aged 18-35 years old who actively use fintech to manage personal finances. Multiple linear regression analysis shows that financial literacy has a significant influence on digital financial well-being, where individuals with higher financial literacy tend to have better financial well-being. Financial behavior proved to be an important mediating variable in linking financial literacy with digital financial well-being, while risk perception negatively influenced the relationship. This result is in line with Protection Motivation Theory which explains that financial literacy helps individuals deal effectively with digital financial risks. The findings have practical implications for formulating more effective digital financial education strategies, as well as making theoretical contributions to the financial management literature. Future research is recommended to explore other factors such as social support and cultural factors in digital financial literacy .